The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/ndt.s325000
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ketamine Infusions in Treatment-Resistant Bipolar Depression: An Open-Label Naturalistic Observational Study

Abstract: Purpose Bipolar disorder is a chronic and recurrent condition often associated with treatment resistance and suicidality. There is an unmet need for effective treatment in this group of patients. Ketamine has been demonstrated to have antidepressant and antisuicidal properties in unipolar depression. Most of the available studies concern unipolar depression. Here, we present the efficacy and safety of IV ketamine as an add-on treatment in patients with bipolar I and bipolar II depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…16 The glutamatergic hypothesis for depressive disorders has been supported by the antidepressant efficacy of ketamine, an antagonist of the ionotropic N-methyl-D-aspartate (NMDA) receptor. 16 Ketamine has shown good efficacy in both bipolar 17,18 and unipolar 19 TRD, with response rates ranging from 50-70%. 20 Furthermore, in the various studies conducted, 18,[21][22][23] no cases of manic switch after ketamine use in B-TRD have been shown, with preliminary data supporting effectiveness and safety among those patients.…”
Section: New Treatment Options Available For Depressive Symptomsmentioning
confidence: 99%
“…16 The glutamatergic hypothesis for depressive disorders has been supported by the antidepressant efficacy of ketamine, an antagonist of the ionotropic N-methyl-D-aspartate (NMDA) receptor. 16 Ketamine has shown good efficacy in both bipolar 17,18 and unipolar 19 TRD, with response rates ranging from 50-70%. 20 Furthermore, in the various studies conducted, 18,[21][22][23] no cases of manic switch after ketamine use in B-TRD have been shown, with preliminary data supporting effectiveness and safety among those patients.…”
Section: New Treatment Options Available For Depressive Symptomsmentioning
confidence: 99%
“…The studies seem to suggest higher response rates than single infusion, but further exploration is needed. 68 , 69 , 71 …”
Section: Resultsmentioning
confidence: 99%
“…The studies seem to suggest higher response rates than single infusion, but further exploration is needed. 68,69,71 Tables 2-4 summarize the available published evidence based on RCTs of the pharmacotherapies for TRBD.…”
Section: Ketamine (Table 4)mentioning
confidence: 99%
“…While these effects traditionally occur during infusion and are usually transient, the psychotomimetic symptoms may be distressing for some individuals who experience significant dissociative symptoms. Studies of ketamine in bipolar depression found similar self-limited psychotomimetic and dissociative symptoms that warrant close safety and tolerability monitoring [ 77 ]. It should be noted that ketamine’s dissociative effects have been investigated as potentially contributing to its antidepressant effects, particularly in the psychotherapy models discussed in Sect.…”
Section: Adverse Effects Of Ketaminementioning
confidence: 99%